A Lack-of-Fit Test for Econometric Applications to Cross-Section Data - Doran, Howard E.; Kmenta, Jan (The Review of Economics and Statistics, 1986)
A bstract-A lack-of-fit test of model specification used by experimental statisticians but mostly unknown to econometricians is presented.The test is applicable in situations in which there are replicated observations on the dependent variable.In this paper the test is modified to allow for heteroskedasticity usually encountered when dealing with cross-sectional observations, and illustrated by an application to an earnings function estimated from a sample survey of Norwegian women.